Participation and democratic innovation under International human rights law - McMurry, Nicholas; McMurry, Nicholas : 2023 (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"This book explores the human rights principle of participation and the human right to participation. The work presents the argument that international human rights law imposes obligations to enable participation, and demonstrates that it has been interpreted in this way by authoritative bodies. Divided into four parts, Part I provides the historical and theoretical background. Part II presents the argument that a right to participation and a human rights principle of participation exist in international law and, in Part III, that human rights law, and the way it has been interpreted, can provide a coherent account of the content of such a right and principle. The conclusions of the book and their implications are explored in Part IV. While there have been several studies of specific forms of participation, such as collective bargaining, this study provides a coherent account of the meaning and application of participation in international human rights law as a whole. The book will be an invaluable resource for academics, researchers and policy-makers working in the area of international human rights law"--
General participatory provisions -- Broad justifications for participation -- Regional instruments requiring participation -- Rights for specific groups and contexts -- Participatory rights in other fields of international law -- Establishing a human rights principle of participation -- Triggers for participation -- Participants -- Implementation of participation -- Consequences of participation -- Enforcement of participation.
Based on author's thesis (doctoral - National University of Ireland, Galway, 2017) issued under title: Deepening democracy : participation under international human rights law.
Includes bibliographical references and index.
Catalography
Keywords: Political rights; Political participation; Human rights -- Political aspects; Right to public participation